2011
DOI: 10.1177/155892501100600306
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Doffing Tube Components for Rotor-Spun Yarn for Weft Knitted Fabrics Using Multi-criteria Decision-making Approach with Interval Data

Abstract: Selecting appropriate spinning conditions according to the properties of the final yarn is an intricate aspect and is inherently a multi-criteria decision-making (MCDM) problem. In recent years, various MCDM approaches have been used for solving such kind of the problems with exact value of the attributes. But, values of the properties for a yarn are affected by some factors such as specimen length, number of tests and experimental conditions. Therefore, decision-makers use average values instead of exact valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The purpose of a sensitivity analysis is mainly to examine whether the data have a significant impact on the results. Using a weight sensitivity analysis, Moghassem and Fallahpour [64] and Moghassem [65] showed whether all the weights of the criteria, 5%, 10%, 15% and 20%, tend to increase or decrease by repeating the TOPSIS approach. Other studies have shown that weight has great effects on the results of TOPSIS [66].…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of a sensitivity analysis is mainly to examine whether the data have a significant impact on the results. Using a weight sensitivity analysis, Moghassem and Fallahpour [64] and Moghassem [65] showed whether all the weights of the criteria, 5%, 10%, 15% and 20%, tend to increase or decrease by repeating the TOPSIS approach. Other studies have shown that weight has great effects on the results of TOPSIS [66].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Other studies have shown that weight has great effects on the results of TOPSIS [66]. Therefore, based on the findings of Moghassem and Fallahpour [64] and Moghassem [65], this study performs a weight sensitivity analysis.…”
Section: Sensitivity Analysismentioning
confidence: 99%